The Portraying Identity through Individual Social Responsibility (ISR): the case study of Vikrom Kromadit / ภาพสะท้อนอัตลักษณ์ด้านการแสดงความรับผิดชอบต่อสังคมในระดับบุคคล (ISR) กรณีศึกษา คุณวิกรม กรมดิษฐ์ - ศรัญญา กิตติวัฒนโชติ ชุติมา เกศดายุรัตน์ และปฐมาพร เนตินันทน์, Saranya Kittiwattanachot, Chutima Kessad (Journal of Community Development Research (Humanities and Social Sciences); Vol 6 No 2 (2556): July - December 2013DO - 10.14456/jcdr.v6i2.604, 2014)
ในการทาความเข้าใจการประกอบสร้างอัตลักษณ์บุคคล จากมุมมองหลังยุคสมัยใหม่ (Postmodern) จาเป็นต้องมีการศึกษาอิทธิพลของกระแสโลกาภิวัฒน์ที่มีต่อบริบททางสังคมที่เปลี่ยนแปลงอยู่ตลอดเวลา ซึ่งเป็นเรื่องที่ท้าทายความสามารถของบุคคลในการบริหารจัดการ รวมถึงการสื่อสารตัวตนเพื่อสร้างความแตกต่างท่ามกลางความหลากหลาย การวิจัยนี้เป็นการศึกษาภาพสะท้อนอัตลักษณ์ในมิติด้านการแสดงความรับผิดชอบต่อสังคมในระดับบุคคล (ISR) ของคุณวิกรม กรมดิษฐ์ ผ่านผลงานเขียน โดยวิธีการวิเคราะห์เนื้อหาจากผลงานเขียนจานวน 5 เล่ม พบว่า อัตลักษณ์เฉพาะของคุณวิกรม กรมดิษฐ์ มีความเชื่อมโยงสัมพันธ์กันระหว่างอัตลักษณ์ส่วนบุคคลและอัตลักษณ์ทางสังคม ซึ่งมิติเรื่อง ISR ถูกสะท้อนให้เห็นว่าเป็นอัตลักษณ์หนึ่ง ซึ่งทาให้เราเข้าใจการนิยามตัวตนของคุณวิกรม ในฐานะผู้นาองค์กรผ่านทางองค์กรอมตะ และมูลนิธิอมตะ โดยมีวิธีการสร้าง และการนาเสนออัตลักษณ์อย่างเป็นกระบวนการ คือ ส่วนที่ 1 การบริหารจัดการเชิงกลยุทธ์ทั้งก่อน และหลังกระแสโลกาภิวัตน์ ส่วนที่ 2 การเลียนแบบผสมผสานภายใต้บริบทเรื่องการสร้างแบรนด์ผู้นาองค์กรธุรกิจผ่านเรื่อง CSR และ ISR ส่วนที่ 3 การนาเสนออัตลักษณ์ที่ลื่นไหลเปลี่ยนแปลงผ่านรูปแบบการสื่อสารความเป็นตัวตน อาทิ ผู้นาองค์กรธุรกิจระดับแนวหน้า, ผู้เชี่ยวชาญในการให้ความรู้วิเคราะห์ปัญหาสังคมและเศรษฐกิจ, ตัวแทนสร้างความร่วมมือและความสัมพันธ์ระหว่างประเทศ, การเป็นคนดีเพื่อตอบแทนสังคม, การวางตัวเป็นแบบอย่างต่อคนในสังคม และนักเดินทางเพื่อแสวงหาประสบการณ์ใหม่ๆ โดยนาเสนอผ่าน 4 ช่องทาง คือ ผ่านสื่อประเภทหนังสือ, สื่อประเภทวิทยุโทรทัศน์, มูลนิธิอมตะ และการทาคาราวาน โดยผลการวิจัยทาให้เห็นอัตลักษณ์บุคคล และอัตลักษณ์ในมิติ ISR ของคุณวิกรมในเรื่องต่างๆ คำสำคัญ: อัตลักษณ์หลังยุคสมัยใหม่ ความรับผิดชอบต่อสังคมในระดับบุคคล โลกาภิวัฒน์ การวิเคราะห์เนื้อหา It is also an area understanding the Postmodern Identity in this new era. An important to include studies of current globalization influence to coexist with social always change situation. The ability challenge is for management Individual include interpersonal communication created between more various. This research is to study Identity reflection of Vikrom Kromadit, who won a writing achievement through his paper “The Portraying Identity through Individual Social Responsibility (ISR)”. From content analysis of the writing achievement, all five of the books found that there is an established relationship between the Individual Identity and Social Identity. Through this dimension of ISR reflection, we are able to have a deeper understanding of Identity and the Individual definition of Vikrom Kromadit, sponsored by the organization leaders of Amata Organization and Amata Foundation. The ways of creation and presentation of processing consists of three parts. Part 1 is the strategic management both before and after the current globalization. Part 2 is the combination imitation under the context of creation branding business  leaders through of CSR and ISR. Part 3 The Identity, channels the change of an Individual through ways of communication such as Business leader’s forefront, or the Expert giving knowledgeable analysis of social and economic problems. The agents created partnerships and international relationships. Be a good person for society, being exemplary for the people in society and travelers seeking the new experience that presents through the four channels: Book Media, Radio and Television Media, and finally the Amata Foundation and Caravan. The research a result defines the Individual and Identity, and reveals and Dimension Identity ISR of Vikrom Kromadit, among other matters. Keywords: Postmodern Identity, Individual Social Responsibility (ISR), Globalization, Content Analysis
Keywords: อัตลักษณ์หลังยุคสมัยใหม่ ความรับผิดชอบต่อสังคมในระดับบุคคล โลกาภิวัฒน์ การวิเคราะห์เนื้อหา Postmodern Identity, Individual Social Responsibility (ISR), Globalization, Content Analysis